Cost-effective whole-cell biosynthesis of ursodeoxycholic acid using engineered Escherichia coli with a multienzyme cascade - Zhang, Xue; Xin, Jiagang; Liu, Mengyu; Zhang, Yue; Luan, Haoni; Feng, Wei; Wang, Fei; Xu, Wei; Song, Peng (Frontiers in Microbiology, 2025)
Ursodeoxycholic acid (UDCA) can be used as a drug to treat various liver and bile diseases. Currently, the biological synthesis of UDCA is predominantly conducted via a two-step enzymatic process in which synthesis is catalyzed by 7α-hydroxysteroid dehydrogenase (7α-HSDH) and 7β-hydroxysteroid dehydrogenase (7β-HSDH) in succession, utilizing chenodeoxycholic acid (CDCA) as the substrate. In this study, an engineered Escherichia coli (E. coli) strain, designated UCA23, was constructed. This strain coexpressed four enzymes under the control of three independent T7 promoters: lactate dehydrogenase (LDH) derived from Lactobacillus delbrueckii, glucose dehydrogenase (GDH) derived from Priestia megaterium, 7α-HSDH derived from E. coli, and 7β-HSDH derived from Ruminococcus torques, enabling the whole-cell catalytic synthesis of UDCA from CDCA. This study systematically optimized the reaction parameters, including temperature, pH, and the addition of organic solvents and surfactants, for the whole-cell catalytic synthesis of UDCA by UCA23, and at the 2 L level, a UDCA conversion rate of 99% was achieved with 100 mM CDCA in 2 h, which is the highest level of conversion of a high-concentration CDCA substrate reported to date.